2017
DOI: 10.3758/s13414-017-1303-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving crowd attention: Gaze following in human crowds with conflicting cues

Abstract: People automatically redirect their visual attention by following others' gaze orientation, a phenomenon called "gaze following." This is an evolutionarily generated socio-cognitive process that provides people with information about their environments. Often, however, people in crowds can have rather different gaze orientations. This study investigated how gaze following occurs in situations with many conflicting gazes. In two experiments, we modified the gaze cueing paradigm to use a crowd rather than a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 60 publications
(74 reference statements)
8
36
0
Order By: Relevance
“…Our finding is broadly consistent with past work on gaze following in human crowds, which showed that reliable gaze following emerged when seven out of 10 (i.e., 70%), but not when six out of 10 agents (i.e., the strict majority of 60%) displayed consistent visual social cues (Sun et al, 2017). Along with our data, this observation also supports a quorumlike principle, as a relevant proportion, rather than a strict majority of social cues, appears to have guided observers' responses in both cases (see also Dyer, Johansson, Helbing, Couzin, & Krause, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding is broadly consistent with past work on gaze following in human crowds, which showed that reliable gaze following emerged when seven out of 10 (i.e., 70%), but not when six out of 10 agents (i.e., the strict majority of 60%) displayed consistent visual social cues (Sun et al, 2017). Along with our data, this observation also supports a quorumlike principle, as a relevant proportion, rather than a strict majority of social cues, appears to have guided observers' responses in both cases (see also Dyer, Johansson, Helbing, Couzin, & Krause, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…3 Example of stimulus configurations for Experiment 2. Depending on the target location, images depict stimulus displays for the zero_ or five_ faces_cuing condition (a), one_ or four_faces_cuing condition (b), and two_ or three_faces_cuing condition (c) follow a Bmajority rule,^in that their attention would become biased toward the gaze direction displayed by the group majority (Sun et al, 2017). In contrast, and offering support for a Bquorum-like^principle, here we show that a minority representation was sufficient to bias observers' attention in a threeperson group (Experiment 1) and that the proportion of gaze cues needed to elicit gaze following was modulated by group size (Experiment 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, research on this topic has shown that the behavior of others is contagious, and that the degree of contagiousness depends on the number of persons taking part (Darley & Latané, 1968;Latane, 1981;Milgram, Bickman, & Berkowitz, 1969). For example, Milgram et al (1969) found in a field study that people were increasingly more likely to copy a group of confederates looking up as the group became larger (see also Capozzi, Bayliss, & Ristic, 2018;Gallup et al, 2012;Knowles & Bassett, 1976;Sun, Yu, Zhou, & Shen, 2017). As argued by the authors, a sensible explanation for this result is that larger groups are imitated more often because they are more likely to be looking at something interesting (Milgram et al, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Crowded multiagent situations are characterized by a potentially overwhelming amount of social information . Here, the three routes of processing appear to allow for effective monitoring and filtering of social cues in order to prevent indiscriminate responses and to maintain a flexibility to focus on relevant social information if needed . In contrast, small groups, typically defined as those composed of 3–5 individuals engaged in a common activity, elicit and afford social interactions that require efficient handling of individual members’ social cues .…”
Section: Attention As a Gate For Social Interactionsmentioning
confidence: 99%